Interactions between children and their early childhood educators: The effect of cultural match on communication. Issue 1 (March 2019) - Webb, Gwendalyn; Williams, Cori
This paper describes the findings of research into children's interactions with educators who were of the same or different culture from that of the children. The research investigated the effect of cultural context on the children's communication and the quality of their interactions in one mainstream early childhood setting. Aboriginal and non-Aboriginal educators were video-recorded interacting with Aboriginal and non-Aboriginal children in an early childhood education and care setting. The interactions between the children and their educators were categorised according to whether the culture of the educator matched that of the child (cultural match), or not (cultural non-match). The interactions were transcribed and the children's communication analysed across a variety of linguistic measures. Results indicated that the children's communication with their educators differed in qualitative but not quantitative measures in response to cultural match. These findings support the need for further research in this area.